Double-Key Secure for N-1-N Sound Record Data (SRD) by the Drive-Response of BAM NNs - Kalpana, Muthusamy; Ratnavelu, Kurunathan; Balasubramaniam, Pagavathi; Othman, Wan Ainun Mior (Springer Verlag, 2019)
In this work, the problem of N sound record data (audio) encryption based on double-key secure is proposed. The first key is the math tricks to cumulate N audio files in a single file. The second key is the values of the parameters A,B,D,A~,B~,D~, of the constructed drive-response bidirectional associative memory neural networks to be found by suitable Lyapunov–Krasovskii functional and satisfying the linear matrix inequality to obtain the dynamical signal (irregular), which are used to encrypt an audio file. Further, the key sensitivity of 1 e- 10 of the proposed method are large adequate key space to make hacker’s attack infeasible. Numerical simulations, cryptanalysis of the proposed scheme are provided to show the best performance. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.